Synchronization of Notary Supervision by Notary Supervision Assembly in Law Enforcement - Suwardi Suwardi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The Notary Institution, one of the social institutions in Indonesia, arises from the need in human relations that requires a means of evidence regarding the civil law relationship that exists and or occurs between them. The authority of a notary is regulated in Article 1 number 1 of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of a Notary (hereinafter abbreviated as UUJN) which states that: